Late Cardiovascular Syphilis - T. V. Krasnosel'skikh; E. V. Sokolovskii; A. Yu. Lonshakova-Medvedeva; D. I. Petuhova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
A case of belatedly diagnosed late cardiovascular syphilis that had continued progressing despite two courses of ceftriaxone therapy is described. The patient had a combination of all possible complications of syphilitic mesaortitis including aortic regurgitation, coronary insufficiency, as well as fusiform aneurysm of the ascending aorta and the proximal aortic arch. Current issues of diagnosis and therapy of late cardiovascular syphilis are discussed.